Euroregiony a cyfryzacja - Greta, Marianna; Tomczak-Woźniak, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Opracowanie zgodnie z tytułem stanowić będzie prezentację wniosków z rozważań nt. potencjalnego wpływu funkcjonowania euroregionu na poziom cyfryzacji w regionach nim objętych. Euroregiony to peryferyjne względem ośrodków wzrostu obszary UE, do których skierowany jest m.in. nowy program unijny „Łącząc Europę”. Program ten ma trzy składowe: e-energia, e-transport i e-cyfryzacja. Założeniem Strategii Europa 2020 jest zbliżenie najbardziej odległych regionów do „serca” UE, czemu służyć ma instrument „Łącząc Europę”, w szczególności element cyfryzacji (w tym Internet szerokopasmowy). W opracowaniu autorzy podejmą próbę odpowiedzi na pytanie, jakich korzyści wykorzystania tych instrumentów można się spodziewać w euroregionach obejmujących polskie obszary.

The study according to the title will constitute the presentation of conclusions from discussions on the potential impact of functioning of the Euroregion to the level of the digitization in regions they embrace. Euroregions are peripheral areas regarding to centres of the growth to which the new EU program Connecting Europe Facility is directed. This program has three elements: e-energy, e-transport and the e-digitization. The aim of the Strategy Europe 2020 is „bringing closer” the most distant regions to EU’s “hearts” and the Connecting Europe Facility serves this purpose, in particular the element of the digitization (including the broadband Internet). In the study Authors will make an attempt to find the answer to a question of what effects of using these instruments it is possible to expect in Euroregions spreading through Polish areas.
Keywords: cyfryzacja; euroregion; Unia Europejska; digitization; Euroregion; the European Union